Dissolving the Engineering Moral Dilemmas Within the Islamic Ethico-Legal Praxes - Solihu, Abdul Kabir Hussain; Ambali, Abdul Rauf (Springerlink, 2009)
The goal of responsible engineers is the creation of useful and safe technological products and commitment to public health, while respecting the autonomy of the clients and the public. Because engineers often face moral dilemma to resolve such issues, different engineers have chosen different course of actions depending on their respective moral value orientations. Islam provides a value based mechanism rooted in the Maqasid al-Shari‘ah (the objectives of Islamic law). This mechanism prioritizes some values over others and could help resolve the moral dilemmas faced in engineering. This paper introduces the Islamic interpretive-evaluative maxims to two core issues in engineering ethics: genetically modified foods and whistleblowing. The study aims primarily to provide problem solving maxims within the Maqasid al-Shari‘ah matrix through which such moral dilemmas in science and engineering could be studied and resolved.